PENGARUH PENGGUNAAN TABUNGAN KEPINGAN TERHADAP DISIPLIN PADA ANAK USIA 4-5 TAHUN DI TK BUNGO SETANGKAI KOTA PAYAKUMBUH - Mulya, Fitriani; Indarto, Wusono; ', Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on the results of field observations to discipline students is still low and teachers still use learning methods that dominate and not varied. So that should be the application of the technique savings pieces. This study aims to determine the effectiveness of the application of the technique savings pieces to discipline children aged 4-5 years in TK Bungo Setangkai, Payakumbuh City. The sample used in this study19 people. The data collection techniques were used that observation. Data were analyzed using t-test using SPSS 20.0. Research hypothesis is that there is a very significant influence on the discipline of the students after applying the technique avings pieces. It can be seen from the analysis of data obtained t = 24.509 and ttabel=2.101 so thitung>ttabel and p = 0.000. Because p < 0.05, it can be concluded that there are differences in discipline very significant protégé after using a savings pieces in learning techniques. So it means that Ho is rejected and Ha accepted which means there is a very significant difference between before and after the experiment by applying the technique savings pieces.Keyword : Discipline, Savings Pieces